Less common manifestations in TSC. Issue 3 (29th August 2018) - Boronat, Susana; Barber, Ignasi
Abstract : Tuberous sclerosis complex (TSC) is due to pathogenic variants in TSC1 or TSC2 genes resulting in hyperactivation of the mTOR pathway. Many organ systems can be affected, such as brain, skin, eye, heart, bone, kidney, or lung. Typical lesions of TSC usually are those included as major criteria, including angiofibromas, hypomelanotic macules, tubers, subependymal nodules, angiomyolipomas, cardiac rhabdomyomas, and lymphangioleiomyomatosis. However, there are many other manifestations less frequent and/or less well known, many of them not included as clinical diagnostic criteria that are part of the clinical spectrum of TSC. The focus of this review will be on these less common and less well‐known manifestations of TSC. Among the rare manifestations, we will discuss some clinical findings including arteriopathy, arachnoid cysts, lymphatic involvement, chordomas, gynecological, endocrine, and gastrointestinal findings. Among the manifestations that are very frequent but much less well known, we find the sclerotic bone lesions. Although they are very frequent in TSC they have been largely overlooked and not considered diagnostic criteria, mainly because they are asymptomatic. However, it is important to know their typical characteristics to avoid misdiagnosing them as metastasis.